On fractional Volterra integrodifferential equations with fractional integrable impulses - Sutar, Sagar T.; Kucche, Kishor D. (Mathematical Modelling and Analysis, 2019)
We consider a class of nonlinear fractional Volterra integrodifferential equation with fractional integrable impulses and investigate the existence and uniqueness results in the Bielecki’s normed Banach spaces. Further, Bielecki-Ulam type stabilities have been demonstrated on a compact interval. A concrete example is provided to illustrate the outcomes we acquired.